2019
DOI: 10.1111/ner.13021
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Effects of Transcutaneous Electrical Acustimulation Combined With Deep Breathing Training on Refractory Gastroesophageal Reflux Disease Mediated via the Autonomic Pathway

Abstract: Aims To investigate the effects and possible mechanisms of transcutaneous electrical acustimulation (TEA) combined with deep breathing training (DBT) on refractory gastroesophageal reflux disease (rGERD). Methods Twenty‐one patients with rGERD were recruited and randomly assigned to receive either only esomeprazole (ESO, 20 mg bid) (group A, n = 7), TEA + DBT + ESO (group B, n = 7), or sham‐TEA + DBT + ESO (group C, n = 7) in a four‐week study. The reflux diagnostic questionnaire (RDQ) score and heart rate var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…TEA has been shown to be effective in improving impaired gastric functions in patients with functional dyspepsia (18) and in patients with diabetic gastroparesis (19). Two studies have reported an increase in LES pressure with TEA in patients with GERD (20,21). However, it is unknown whether TEA might also be effective in treating IEM in patients with GERD.…”
Section: Introductionmentioning
confidence: 99%
“…TEA has been shown to be effective in improving impaired gastric functions in patients with functional dyspepsia (18) and in patients with diabetic gastroparesis (19). Two studies have reported an increase in LES pressure with TEA in patients with GERD (20,21). However, it is unknown whether TEA might also be effective in treating IEM in patients with GERD.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al recruited 21 patients with refractory GERD for a 4 weeks study, and the results showed that TEA combined with deep breathing training could effectively improve reflux symptoms and increase LES pressure. This effect may be mediated by autonomic nervous and intestinal mechanisms 31 …”
Section: Discussionmentioning
confidence: 99%
“…This effect may be mediated by autonomic nervous and intestinal mechanisms. 31 The TN technique used in this study is a non-invasive method for nerve electrical stimulation, which combines electrical stimulation with acupuncture points and has been applied in clinical practice. Ge…”
Section: Discussionmentioning
confidence: 99%
“…The watch-size stimulator was maintained at 25 Hz (5 mA), for 30 minutes twice a day, with the stimulation parameters being programmed using a specific computer. The same parameters were used for Sham-TEA which was performed at a nonchannel and noncollateral nonacupoints 2 cm away from ST36 and PC6 acupoints [ 21 ].…”
Section: Methodsmentioning
confidence: 99%